Optimization of E-Tilang System Implementation to Build a Culture of Order and Legal Compliance Among Road Users at Bogor Police - Prihandono, Yoga (Advances in Police Science Research Journal, 2024)
This research is motivated by problems related to the high growth in the number of motor vehicles, especially in the district. Bogor which has an impact on increasing violations on the highway as a result of the lack of public legal awareness in complying and implementing traffic laws. As for problems related to traffic violations, among others, ranging from speed violations, overloading, completeness of vehicles and documents, seat belts, violations of roads signs / markers, against the flow, not wearing a helmet, pillion with more than 1 (one) person, and etc. Therefore, to overcome these problems, one of the ways implemented by the Bogor Police is by implementing the E-ticketing system. This study aims to determine the implementation of the e-ticketing system in building an orderly and law-abiding culture of the people in Kab. Bogor. This study uses a qualitative approach with field research methods, where the findings in this study indicate that the implementation of the E-ticketing system at Bogor Police Station has not been effective and efficient due to the fact that the public still prefers a manual / conventional ticketing system because it is considered more cheap cost of ticket fines so that it does not cause a deterrent effect for the community of road users who commit traffic violations, internet networks that are less strong in the suburbs, form filling applications for E-Tilang are considered still not simple. So as to make the E-ticket application more effective in Bogor District Police, collaboration with various parties is needed.